From filth-ghost to Khmer-witch: Phi Krasue’s changing cinematic construction and its symbolism - Baumann, Benjamin (Horror studies, 2014)
Depicted as a floating woman’s head with drawn out and bloody entrails dangling beneath it, phi krasue is one of the most iconic uncanny creatures of Thai horror cinema. However, despite its position as one of Thailand’s most striking and well-known phi, there is very little - research investigating this specific phenomenon. This is remarkable given the commonality of encounters with this uncanny being in ‘real life’ and the continuous presence of its ghostly images in popular cultural media. Relating empirical data gathered during anthropological fieldwork - in a rural community of Thailand’s lower north-east to the analysis of two Thai ghost films that take this ghostly image as their main subject and narrative force this article argues that the knowledge of vernacular ghostlore is essential to decipher the cinematic representations’ - full symbolism. Thai ghost films are produced for the ‘knowing spectator’ who has implicit knowledge of the cultural logics structuring ghostly classification in contemporary Thailand. This embodied knowledge allows Thai audiences to make sense of phi krasue’s ghostly image - despite its cinematic transformation from ‘Filth Ghost’ to ‘Khmer Witch’. Based on Kristeva’s theory of abjection I will show that Thai audiences continue to see phi krasue first and foremost as uncanny ‘matter out of place’.